2008
DOI: 10.1055/s-0028-1098738
|View full text |Cite
|
Sign up to set email alerts
|

Sind elektive Lymphknotendissektionen in der Karzinomchirurgie noch zeitgemäß?

Abstract: The gene-based control of metastases implies a principal process of metastatic spread for solid tumours. The hypothesis "metastases do not metastasise" has a high plausibility. Reduction of lymph node dissection and its performance only in those cases where it is necessary for treatment decisions seems to be (bio)-logically consequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
7

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
1
0
7
Order By: Relevance
“…Up to now there is no meta-analysis consistent randomized study for any tumor (LoE 1A study) that confirms the prognostic benefit of elective lymph node dissection [131]. An extensive review article analyses the significance of lymphadenectomy in solid tumors and revealed that lymph node dissection does not lead to a significant improvement of the total survival [132].…”
Section: Prognostic Relevance Of Neck Dissectionmentioning
confidence: 99%
“…Up to now there is no meta-analysis consistent randomized study for any tumor (LoE 1A study) that confirms the prognostic benefit of elective lymph node dissection [131]. An extensive review article analyses the significance of lymphadenectomy in solid tumors and revealed that lymph node dissection does not lead to a significant improvement of the total survival [132].…”
Section: Prognostic Relevance Of Neck Dissectionmentioning
confidence: 99%
“…Wenn die Metastasen nicht metastasieren und sich unabhängig von ihrem Primärtumor entwickeln, stellt sich die Frage, ob bei Kopf-Hals-Karzinomen die Neck dissection das Risiko für die hä-matogene Metastasierung und die Prognose der betroff enen Patienten beeinfl ussen kann. Es gibt zurzeit zu keinem Tumor eine Metaanalyse konsistente randomisierte Studie (LoE 1 A-Studie), die den prognostischen Nutzen der elektiven Lymphknotendissection belegt [ 131 ] . Eine ausführliche Übersichtsarbeit analysierte die Bedeutung der Lymphadenektomie bei soliden Tumoren und stellte fest, dass Lymphknotendissection keine signifikante Verbesserung der Gesamtüberlebensrate bewirken kann [ 132 ] .…”
Section: Prognostische Bedeutung Von Neck Dissection ▼unclassified
“…Auch in der chirurgischen Literatur wird von Einzelnen eine "radikale" Lymphknotendissektion abgelehnt, ohne dass Gründe genannt werden oder obwohl sogar aus den eigenen Daten der Autoren eindeutig Argumente für eine radikale Lymphknotendissektion abzuleiten wären [10,23].…”
Section: Argumente Gegen Eine Lymphknotendissektionunclassified